2021
DOI: 10.47115/bsagriculture.841263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Forcing of Corms on The Flowering of Saffron (Crocus Sativus L.)

Abstract: Among all environmental factors, the temperature is considered one of the key elements that control the growth and development of saffron. This study was undertaken to investigate the effect of thermal forcing of corms on saffron growth and development. To this end, mother corms were collected at four different periods: late March (T2) , mid-April (T3) , late April (T4), and after leaf senescence (Control, T1) . The corms of each period were then pretreated at three successive temperature levels: at 25 °C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Moreover, the plant is reported to be adaptable to various environmental conditions. It grows well in arid and semi-arid areas as it can adapt to temperate and subtropical climates [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the plant is reported to be adaptable to various environmental conditions. It grows well in arid and semi-arid areas as it can adapt to temperate and subtropical climates [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…To a certain extent, frost during the period of flowering could be detrimental as the flowers were unable to bloom and the stigmas shrivelled, which in turn reduced saffron productivity (McGimpsey et al, 1997). According to Mzabri et al (2021), cold storage of the C. sativus corms at 4°C for 7 and 14 days which were even shorter than the storage duration (8 weeks) applied in the present study, had harmed the flower and stigmas production. The cold period before growth at 10°C or 17°C also delayed the flowering in other crocuses such as C. nevadensis and C. vernus (Pastor-Ferriz et al, 2021).…”
Section: Effect Of Temperatures On Floweringmentioning
confidence: 56%
“…Saffron (C. sativus L.) (Iridaceae) is a sterile geophyte with autumnal flowering and asexually reproduced only through corms. It has been reported that C. sativus grows well into various environmental conditions from temperate to subtropical climates and from arid to semi-arid regions (Mzabri et al, 2021b), exhibiting higher yields under rainy autumn, mild winter, and warm summer climatic conditions (Ahmad et al, 2013). In major saffron producing countries, particularly in Iran and India, there are more than 95,000 farm families associated directly or indirectly with the crop.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%